Proximate composition and functional properties of banana flour at different ripening stages - Lanny Sapei (Jurnal Litbang Industri, 2023)
Bananas commonly grow in tropical areas and have many health benefits derived from both the inner and outer parts of the fruit. The proximate composition and functional properties of banana flour with varying ripening stages of plantain banana fruit (green, green-yellow, yellow-green) were studied in this research. Banana was peeled prior to drying and milling into flour followed by starch extraction. Besides proximate analysis, the yields of the obtaining banana flour and starch, as well as the functional properties of starch such as solubility, swelling power, and pasting properties, were also determined. The total carbohydrate, crude fiber, and ash content tended to decrease with the ripening process, in contrast, fat, protein, and moisture content tended to increase over ripening. The amylose/amylopectin content of banana starch influenced the functional properties such as solubility, swelling, and pasting profiles. However, there were no significant differences in the chemical compositions and functional characteristics of banana flour compared with its ripening stage (P>0.05) based on Kruskal-Wallis non-parametric statistical tests. Indeed, the information about chemical characteristics and functional properties of banana flour and starch during fruit ripening is important for the banana fruit processing and their product quality assurance.